Subjektiivisen hyvinvoinnin osa-alueiden rakentuminen työmarkkinatukea ja peruspäivärahaa saavilla työttömillä - Aarnio Johanna; Kangas Olli; Ylikännö Minna (Terveyden ja hyvinvoinnin laitos, 2022)
ENGLISH SUMMARY
Johanna Aarnio & Olli Kangas & Minna Ylikännö: The construction of dimensions of subjective well-being among unemployed persons receiving basic unemployment benefits in Finland (Subjektiivisen hyvinvoinnin
osa-alueiden rakentuminen työmarkkinatukea ja peruspäivärahaa saavilla työttömillä) In this article we examine the construction of different dimensions of subjective well-being among unemployed persons receiving basic daily allowance andlabour market support from Kela. We know from earlier research that on average, the unemployed have lower subjective well-being than the employed. However, some people maintain a good level of subjective wellbeing even during unemployment. We are interested to find out how the construction of well-being in this group of people differs from the construction of well-being in other unemployed groups: How are the different dimensions of subjective well-being constructed in these two groups of unemployed persons? Nationally representative data were collected from 946 recipients of basic unemployment benefits in Finland in 2017. The data were analysed using structural equation
modelling (SEM) with confirmatory factor analysis. The dimensions of subjective well-being are
differently constructed in the two unemployed groups. In contrast to the group with high subjective well-being, all dimensions of well-being are interconnected in the lower subjective well-being group. In the group of high subjective well-being, the dependencies between the different dimensions of well-being are 1) the dimension of health and work ability and the standard of living, and 2) the dimension of mental well-being and social capital.
Keywords: unemployment, well-being, subjective well-being, dimensions of well-being.